2017
DOI: 10.1016/j.jval.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Device-Aided Treatments Indicated for Advanced Parkinson Disease

Abstract: This study clarifies the patient perspective in therapeutic choices for advanced PD. These findings may help improve communication between patients and providers and also provide evidence on patient preferences to inform regulatory and access decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…age, magnitude of levodopa responsiveness) may add expert consideration to local guidelines and best medical practices for the use of appropriate device-aided therapies in the treatment of APD patients. In addition, initiation of device-aided therapies should also consider patients' preferences for treatment attributes and risks 34,44 , as well as overall living conditions (e.g. the presence of caregiver/family support, access to a treatment center).…”
Section: Discussionmentioning
confidence: 99%
“…age, magnitude of levodopa responsiveness) may add expert consideration to local guidelines and best medical practices for the use of appropriate device-aided therapies in the treatment of APD patients. In addition, initiation of device-aided therapies should also consider patients' preferences for treatment attributes and risks 34,44 , as well as overall living conditions (e.g. the presence of caregiver/family support, access to a treatment center).…”
Section: Discussionmentioning
confidence: 99%
“…Transitioning from oral drug administration to more invasive measures is an important step for patients; therefore, it is not surprising that many patients initially decline to move forward with DAT or request more time to discuss and educate themselves prior to initiating the change in treatment. The large percentage of patients delaying their DAT initiation suggests a need for enhanced patient-physician guidance on navigating the transition to DAT for optimal patient outcomes, while still incorporating patient preferences [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the uncertainty around DBS efficacy is that patient goals of surgical therapy may not align with what DBS can reasonably offer. Up to 25% of patients may still express dissatisfaction with DBS despite improvement of motor control (26), as patients tend to desire treatments that improve non-motor symptoms as well (27). Research has found that non-motor symptoms, which are not directly improved by DBS, are negatively associated with patient quality of life (28).…”
Section: Impressions Of Dbs Efficacymentioning
confidence: 99%